Chronic metabolic stress impairs lymphatic contractility via activation of KATP channels in a mouse model of Type-2 diabetes - Castorena-Gonzalez, Jorge A.; Kim, Hae Jin; Davis, Michael J. (Frontiers in Physiology, 2025)
IntroductionChronic metabolic stress is a common underlying factor of multiple diseases, including obesity, type II diabetes, and metabolic syndrome. Lymphatic dysfunction, including valve defects, impaired contractile activity, and hyperpermeability, is also associated with these same diseases. We recently reported that acute metabolic stress leads to activation of KATP channels in lymphatic muscle cells, resulting in impairment of the intrinsic lymphatic pacemaker that drives their spontaneous contractions and active lymphatic pumping.MethodsIn the present study, we tested whether lymphatic contractile dysfunction occurs in the db/db mouse, a model of metabolic syndrome, and, if so, to what extent dysfunction might be mediated by KATP channel activation. Contractile function was assessed ex vivo in cannulated and pressurized popliteal collecting lymphatics from age-matched db/db mice or their BKS controls (from males and females at 18–20 weeks of age).ResultsVessels from db/db mice exhibited pressure-dependent spontaneous contractions that were significantly reduced in amplitude, frequency, and calculated fractional pump flow at all tested pressures in the range 0.5 to 5 cmH2O, compared to BKS controls. The impaired contractile function of lymphatic vessels from db/db mice was improved by the KATP channel inhibitor glibenclamide (GLIB) at a concentration (1 mM) previously shown to have little or no off-target effects on lymphatic function. Because db/db mice are both obese and have elevated blood glucose levels, we tested whether elevated glucose per se altered contractile function. In glucose levels characteristic of diabetic animals (23 mM), the contraction frequency and fractional pump flow of lymphatic vessels from WT mice were significantly decreased compared to those observed in normal (5 mM) glucose concentrations. The equivalent concentration of mannitol, an osmotic control, did not result in any significant changes in lymphatic contractile function. Lymphatic dysfunction induced by high glucose was rescued by GLIB (1 mM), and lymphatic vessels from Kir6.1−/− mice were largely resistant to the inhibitory effects of high glucose.DiscussionOur results suggest that a substantial fraction of lymphatic contractile impairment in db/db mice is mediated by the activation of KATP channels in lymphatic muscle cells, in part due to chronic metabolic stress associated with elevated glucose.